De novo Transcriptome Sequencing to Dissect Candidate Genes Associated with Pearl Millet-Downy Mildew (Sclerospora graminicola Sacc.) Interaction - Kulkarni, Kalyani S.; Zala, Harshvardhan N.; Bosamia, Tejas C.; Shukla, Yogesh M.; Kumar, Sushil; Fougat, Ranbir S.; Patel, Mruduka S.; Narayanan, Subhash; Joshi, Chaitanya G. (Frontiers in Plant Science, 2016)
Understanding the plant-pathogen interactions is of out most importance to design strategies for minimizing the economic deficits caused by pathogens in crops. With an aim to identify genes underlying resistance to downy mildew, a major disease responsible for productivity loss in pearl millet, transcriptome analysis was performed in downy mildew resistant and susceptible genotypes upon infection and control on 454 Roche NGS platform. A total of ~685 Mb data was obtained with 1 575 290 raw reads. The raw reads were pre-processed into high-quality (HQ) reads making to ~82% with an average of 427 bases. The assembly was optimized using four assemblers viz. Newbler, MIRA, CLC and Trinity, out of which MIRA with a total of 14.10 Mb and 93787 transcripts proved to be the best for assembling reads. Differential expression analysis depicted 1396 and 936 and 1000 and 1591 transcripts up and down regulated in resistant inoculated/resistant control and susceptible inoculated/susceptible control respectively with a common of 3644 transcripts. The pathways for secondary metabolism, specifically the phenylpropanoid pathway was up-regulated in resistant genotype. Transcripts up-regulated as a part of defence response included classes of R genes, PR proteins, HR induced proteins and plant hormonal signalling transduction proteins. The transcripts for skp1 protein, purothionin, V type proton ATPase were found to have the highest expression in resistant genotype. Ten transcripts, selected on the basis of their involvement in defence mechanism were validated with qRT-PCR and showed positive co-relation with transcriptome data. Transcriptome analysis evoked potentials of hypersensitive response and systemic acquired resistance as possible mechanism operating in defence mechanism in pearl millet against downy mildew infection.